The evolution of the institutional investment framework in algeria: rent administration versus private capital? - MOULAI, Kamel (Journal of Excellence for Economics and Management Research, 2022)
The Algerian economy configuration is describes as "Dutch disease" or as a "rentier state". The State of Algeria seems to use the distribution of the rent to cover up the poor quality of institutions. After the 1986’s oil counter shock, Algeria implemented structural and economic reforms in its economy. The objective was to achieve the transition from a planned to a market economy, as well as from the rent economy to a productive one. However, the Algerian economy is still suffering from the crisis of productive investment (currently less than 3% of GDP in industry and services). This article is an attempt to assess the specificity of the institutional reform process that related to productive investment. It shows the influence of oil rent revenues fluctuation on this process. It reveals in particular that the State tends to involve private capital when oil prices drop, but does without it when they increase